PENGEMBANGAN BUKU TEKS BAHASA INDONESIA BERBASIS BUDAYA JAWA TIMUR DENGAN MODEL PAKEM UNTUK PENINGKATAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Wicaksono, Antonius Alam; Bariska, Hanif Fikri (Universitas Nusantara PGRI Kediri, 2018)
A common purpose in this research is to develop text book of Indonesian language based culture East Java with PAKEM model to improve study results students class 4 primary school. As for a special purpose of this research is: (1) described the process develop text book Indonesian language based culture East Java with PAKEM model to improve study results students class 4 elementary school (2) described the quality of the text book of Indonesian language based culture East Java with PAKEM model. This research including the kind of research of development by design 4D model. Development standard covering specific stage, design, and development. The result of developing shows that the development of covering standard definition stage with the results in the form of a map learning needs; the stage design with the results of the draft a text book; and phase of development by teaching design the final text book. The quality of the text book that have been developed are considered to be of the components in the teaching material, the appearance of, language, and graphic. Each of the components won a high percentage 97,9%, 100%, 96,4%, and 93,8% .The acquisition observations in the class IV on the activities of teachers is 92.5 % and results of learning outcome increased by 18 point. Keywords: text book, PAKEM model, learning outcome